POJOK LITERASI UNTUK MENINGKATKAN MINAT BACA SISWA KELAS III MI ALMOURKY - Ni Luh Rini Puspita; Putri Almaidah; Witnansih Rahmatya Tanaiyo; Roswita A Dunggio; Abdul Rahmat; Isnanto Isnanto (Asosiasi Dosen Muda Indonesia, 2022)
In the process of teaching and learning, one aspect that cannot be separated is the ability to read. Every student has a variety of reading interests, and reading is an entry point for knowledge-based information. The capacity to understand what is written and read is clearly influenced by this interest. To increase students' interest in reading, elementary school students must get used to it. The Literacy Corner in the classroom is an important component that cannot be separated from the activities used for teaching and learning. The second grade students of Madrasah Ibtidaiyah Al Mourky became the focus of this research. The method of collecting data through direct observation and documentation is the subject of research. The information obtained was then subjectively investigated, showing that, first, the proficiency angle is a serious emphasis on adjustment exercises that have just been carried out before teaching and learning exercises begin. Second, students can be more interested in reading if they have access to a literacy corner that they can use every day.